2019
DOI: 10.1111/desc.12858
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic background, nonverbal IQ and school absence affects the development of vocabulary and reading comprehension in children living in severe poverty

Abstract: Few studies have examined how socioeconomic status (SES) affects two essential parts of human development, namely vocabulary and reading comprehension, in children facing severe poverty. The Roma population is the largest minority group in Europe, the majority of whom live in severe poverty. This study compared the development of 322 Roma children with the development of 178 non‐Roma children, between the ages of 7 and 10 years, living in Romania. The Roma children had poorer initial vocabulary and reading com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 61 publications
(108 reference statements)
1
47
0
Order By: Relevance
“…In effect, reading comprehension is analyzed by different researchers for whom several factors such as vocabulary knowledge (Laufer, & Avaid-Levitzky, 2017;Perfetti & Stafura, 2014;Quinn, et al, 2015;Van Steensel, et al, 2016;Zhang, 2012;Zhang, & Yang, 2016), grammar knowledge (Leeser, 2007), extensive or intensive reading (Suk, 2017)or the individual factors (Lervåg, et al, 2019) and strategies training (Boulware-Gooden, et al, 2007;Hawkins, et al, 2010; are among the factors influence the development of reading comprehension. The following sheds light on some of such studies.…”
Section: International Journal Of Humanities Social Sciences and Educmentioning
confidence: 99%
See 1 more Smart Citation
“…In effect, reading comprehension is analyzed by different researchers for whom several factors such as vocabulary knowledge (Laufer, & Avaid-Levitzky, 2017;Perfetti & Stafura, 2014;Quinn, et al, 2015;Van Steensel, et al, 2016;Zhang, 2012;Zhang, & Yang, 2016), grammar knowledge (Leeser, 2007), extensive or intensive reading (Suk, 2017)or the individual factors (Lervåg, et al, 2019) and strategies training (Boulware-Gooden, et al, 2007;Hawkins, et al, 2010; are among the factors influence the development of reading comprehension. The following sheds light on some of such studies.…”
Section: International Journal Of Humanities Social Sciences and Educmentioning
confidence: 99%
“…Having explored the impact of socioeconomic status on reading comprehension and vocabulary development, Lervåg et al (2019) showed that socioeconomic status "had a direct influence on growth in both reading comprehension and vocabulary" where they are "partly mediated by school absence and nonverbal IQ" (Lervåg et al, 2019, p.1).…”
Section: International Journal Of Humanities Social Sciences and Educmentioning
confidence: 99%
“…Numerous studies included in this issue present adaptation and/ or testing of behavioral and neuroimaging measures to ensure that these are locally appropriate, feasible, and acceptable for measurement of children's behavioral (Milosavljevic et al, ; Obradović et al, ; Willoughby, Piper, Oyanga, & Merseth, ), language (Dulay, Cheung, & McBride, ; Jasińska, Wolf, Jukes, & Dubeck, ; Knauer, Kariger, Jakiela, Ozier, & Fernald, ; Lervåg, Dolean, Tincas, & Melby‐Lervåg, ), and neural development (Lloyd‐Fox et al, ; Perdue et al, ; Pyykkö et al, ; Turesky et al, ; Wijeakumar, Kumar, M. Delgado Reyes, Tiwari, & Spencer, ). Milosavljevic et al (), for example, test the adaptation of the Mullen Scales of Early Learning in the Gambia and cast light on developmental patterns in children aged 5–24 months.…”
Section: Introduction To Special Issue On Global Child Development Stmentioning
confidence: 99%
“…With regard to longitudinal work, Wolf and McCoy () use cross‐lagged panel analysis to examine bidirectional associations among Ghanaian children's executive functions, and social‐emotional, early literacy, and early numeracy skills over three waves of data. Lervåg et al () examine growth in vocabulary and reading skills over five waves of data collected in Roma and non‐Roma children to examine mediators linking poverty with poor language outcomes. Increased attention to biological embedding of early experience, children's emotional outcomes, and longitudinal investigation of developmental changes are positive and welcome trends in global child research.…”
Section: Introduction To Special Issue On Global Child Development Stmentioning
confidence: 99%
See 1 more Smart Citation